Mentoring for the VI East Java Teaching Team Sports Basketball Banyuwangi Regency - Ach. Zayul M; Galih Farhanto; Donny Setiawan (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2020)
Porprov VI East Java Province will be held in four districts namely Gresik, Bojonegoro, Tuban and Lamongan. Banyuwangi Regency participates in this multi-event sports event held every 2 years with great enthusiasm. Where preparation as well as pre Porprov has been followed. One of the sports that is attracting enough attention is the women's Basketball sports. Where in the pre-warm-up event Porprov was able to wipe out all matches with a win. Plus in this generation there are 2 heroines from Gandrung who represent East Java to take part in Pre-PON, adding to the solid Banyuwangi women's basketball team. Naturally, the management of the coach is targeting this team to enter the final round in this VI VI porprov. In this Porprov we provide assistance to the women's basketball coach team to help maintain the physical and psychological condition of the athletes in attending this event. With a fairly tight schedule to compete 1 time a day makes the athlete's physical and psychological decline. So we provide the right method to recover physically and psychologically from athletes who face a hectic schedule. The method for carrying out this activity is (a) the preparation phase (b) the implementation phase of the mentoring at each match (c) the evaluation phase, which is to make a final report. The results of this mentoring activity were very positive, this can be seen (1) the Banyuwangi basketball women's team entered the final round and won the silver medal (2) the physical and psychological condition of the athlete was always maintained every day proved that there were no athletes who were injured and under perform, (3) the assistance process went smoothly without any significant obstacles.